From values to action the four principles of values-based leadership - Kraemer, Harry M. Jansen (San Francisco Jossey-Bass, 2011)
"Respected former CEO, professor, and speaker examines what it takes to become a values-based leader In this highly-anticipated book, Harry Kraemer argues that today?s business environment demands values-based leaders who, in "doing the right thing," deliver outstanding and lasting results. The journey to becoming a values-based leader starts with self-reflection. He asks, "If you are not self-reflective, how can you know yourself? If you do not know yourself, how can you lead yourself? If you cannot lead yourself, how can you lead others?" Kraemer identifies self-reflection as the first of four principles that guide leaders to make choices that honor their values and candidly recounts how these principles helped him navigate some of the toughest challenges he faced in his career. Offers a framework for adopting the principles of values-based leadership?self-reflection, balance, true self-confidence, and genuine humility?to lead organizations effectively Based on Kraemer?s popular Kellogg MBA course on values-based leadership A recognized expert in values-based leadership, Kraemer is a sought after speaker on the subject Lively and engaging, Kraemer?s book comes at a critical time when true leadership in every facet of society is desperately needed."
Index
Keywords: Leadership